Determinants of CERDIK Behavior and Their Impact on Medication Adherence among Hypertensive Patients: A Community-Based Study in Badung, Bali - I Putu Agus Arsana; I Gede Sathya Agastya; Yohana Virda Eka Setiawati; Arten Romario Aragae; I Putu Sejiwan (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
Hypertension is a non-communicable disease with the most prevalence in the world. In Pelaga Village and Belok Village, 81,92% of the 100% target for hypertension patients undergo regular treatment. In relevance to actualize SDGs goal 3 (good health and well-being), the government program